THE ROLE AND IMPORTANCE OF USING LEADERSHIP METHODS IN THE ORGANIZATION AND MANAGEMENT OF PEDAGOGICAL PROCESSES (Conferencea, 2023)
Leadership is the key factor in organizing managing and uplifting an organization. It has wider implications for every aspect of life, especially in the educational paradigm. Where appropriate, standardized, effective, and advanced knowledge is necessary to meet the international national, and scientific demands of society. Therefore, educational management is required that is associated with leadership style opportunities and role identification.